Protocol for analyzing γδ T cells from the vagina of diet-induced obese mice using single-cell RNA sequencing and flow cytometry - In Kang; Jang Hyun Park; Yumin Kim; Myoung Seung Kwon; Heung Kyu Lee (STAR Protocols, 2023)
Summary: Obesity affects susceptibility to sexually transmitted diseases like genital herpes, caused by herpes simplex virus (HSV) 2. The γδ T cells in the vagina play a major role in HSV-2 suppression. Here, we present a protocol for inducing HSV-2 infection intravaginally in high-fat diet-induced obese mice. We describe steps for isolating single cells from vaginal tissue and analyzing cells using single-cell RNA sequencing and flow cytometry. We then detail confirmation of the γδ T cell phenotype in vitro.For complete details on the use and execution of this protocol, please refer to Park et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.